ECOLOGICAL FUNCTIONS OF MANGROVE BASED ON CARBONDIOXIDE ABILITIES AND CARBON STORAGE AT CENGKRONG BEACH, TRENGGALEK REGENCY - Abdulkadir Rahardjanto; Ulpa Riski Kumala Sari; Lud Waluyo; H. Husamah (Jurnal Biosilampari : Jurnal Biologi, 2022)
The decline in the ecological function of mangroves is due to the reduced area of ​​mangroves in Cengkrong Beach, Trenggalek Regency due to deforestation, to improve environmental quality, the researcher wants to examine the ecological function of mangroves in carbon absorption and carbon storage. The purpose of this study was to analyze the ecological function of mangroves based on the ability to absorb carbon dioxide and to analyze the carbon storage capacity of mangrove forest stands at Cengkrong Beach, Trenggalek Regency. This type of research is descriptive quantitative. The population in this study were all types of mangrove trees and litter in the research plot. Research on tree diameter, tree species and number, wet weight of litter was carried out randomly using simple random sampling. The data analysis technique was correlation test using SPSS 21. The results found 8 types of mangroves, namely Avicennia marina, Bruguiera gymnorrizha, Ceriops decandra, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, and Sonneratia caseolaris. Carbon sequestration in Cengkrong, Trenggalek Regency has a total average of 33.963.42 tons/ha per year, equivalent to standing biomass of 20.136.6 tons/ha. The carbon storage capacity of trees is 9.262.9 tons C/ha, while the carbon storage capacity of litter is 225.48 tons C/ha.